The stories Julian tells - Cameron, Ann, 1943-; Strugnell, Ann (New York : Random House, 2006)
Relates episodes in seven-year-old Julian's life which include getting into trouble with his younger brother Huey, planting a garden, what he did to try to grow taller, losing a tooth, and finding a new friend.
"A stepping stone book."
Keywords: Families -- Fiction; Friendship -- Fiction; African Americans -- Fiction